Biosynthesis, characterization and antibacterial activity of silver nanoparticles by the Arctic anti-oxidative bacterium Paracoccus sp. Arc7-R13 - Zheng Zhang; Shuang Li; Xiaoqian Gu; Jiang Li; Xuezheng Lin (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Silver nanoparticles (AgNPs) have attracted wide interest due to its broad range of applications. This study aims to describe the biosynthesis of AgNPs using an Arctic anti-oxidative bacterium Arc7-R13 and to study its characteristics and antibacterial activity. The biosynthesis of AgNPs was verified using UV–Vis spectrum with the maximum absorption at 416 nm. The morphology of the silver nanoparticles was characterized by TEM and its characterization were investigated by EDX and FTIR. Phylogenetic analysis based on 16S rRNA gene sequence showed that strain Arc7-R13 was affiliated with genus Paracoccus. TEM analysis revealed that the AgNPs synthesized by strain Arc7-R13 were spherical and ellipsoidal in shape with size ranging from 2 to 25 nm. The optimal concentration of AgNO3 and temperature for the biosynthesis were 4 mmol/L and 37 °C, respectively. EDX analysis verified the presence of the element silver in the biosynthesized AgNPs. FTIR analysis revealed that the specific functional groups, OH, CH3 and C≡N, might be responsible for reduction and stabilization of AgNPs. Antimicrobial test showed that the AgNPs had strong antimicrobial activity against all kinds of strains investigated, including Gram-positive Bacillus subtilis, Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa, Escherichia coli.